Analysis of Landscape Architecture Planning and Design Under the Background of Multimedia Based on Swarm Intelligence Optimization Path Algorithm - Zhang, Huawei (Informatica, 2024)
Computer technology has brought greater convenience and effect to landscape architecture design. A multimedia-based landscape architecture method based on the optimization calculation method of swarm intelligence is proposed in this paper. Composition is performed through creation of the environment for the landscape architecture; then the landscape architecture processing in the basic classic multimedia environment is compared and analyzed; meanwhile updated methods are provided. The experimental results prove that compared with the traditional way of calculation and planning, the calculation method using the swarm intelligence optimization path has a smaller comparison of path length and can meet the design and planning standards of landscape architecture.